THE ROLE OF LEAN MANUFACTURING IN ADOPTING NEW PRODUCTS APPLICATION STUDY OF A SAMPLE OF EMPLOYEES OF ALITTIHAD FOOD INDUSTRIES CO. LTD. IN BABIL GOVERNORATE (World Bulletin of Management and Law, 2022)
The current research aims at measuring the role of the Lean Manufacturing in the adoption of new products by a sample of workers at Al-Ittihad Food Industries Co. Ltd. in Babil governorate, and therefore the resolution tool was used to measure the availability of search variables. In order to collect the data, the opinions of a sample of the workers of the Federation Food Industries Limited were surveyed (116) and a valid questionnaire form for analysis, and it was also claimed that the nature of the results sought by the research was revealed in order to use a range of statistical tools, namely the Kronbach Alpha coefficient, the arithmetic mean, and the standard deviation. Pearson's correlation coefficient, regression coefficients), The results showed that there is a link and a significant statistically significant influence between the light manufacturing and the adoption of new products, pointing to the company's workers' interest in producing products free of harmful substances and improving the efficiency of its products through the use of production packages that do not harm the environment. The company also recommends that care be taken to improve workers' environmental knowledge by reducing environmental imbalance, hindering environmental pollution and depleting environmental resources as a result of inaccurate use.